2022
DOI: 10.1111/jne.13064
|View full text |Cite
|
Sign up to set email alerts
|

The effects of somatostatin analogues on glycaemia in the treatment of neuroendocrine tumours

Abstract: Neuroendocrine tumours (NETs) are a subtype of neuroendocrine neoplasms (NENs), comprising a relatively rare and heterogenous tumour type causing approximately 2% of malignancies in the USA. 1 NENs, defined by the World Health Organization as epithelial neoplasms with predominant neuroendocrine differentiation, arise in most organs of the body. NETs are defined as well differentiated (low to mid-grade) neuroendocrine neoplasms, with poorly differentiated NENs being known as neuroendocrine carcinoma. 1,2 NETs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Emerging work is highlighting the complexities of the exocrine–endocrine interface of the pancreas, and whilst response to SSAs can vary, a significant impairment of glycaemic control can occur [ 36 , 37 , 38 ]. Such variability may be the consequence of a balance of inhibitory effects on the pancreatic beta cells, leading to reduced insulin secretion, and the reduction in circulating growth hormone and insulin-like growth factor-1, resulting in reduced insulin requirements [ 38 ]. Rinzivillo et al [ 16 ] demonstrated HbA1C is associated with an increased risk of PEI development after commencing SSA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging work is highlighting the complexities of the exocrine–endocrine interface of the pancreas, and whilst response to SSAs can vary, a significant impairment of glycaemic control can occur [ 36 , 37 , 38 ]. Such variability may be the consequence of a balance of inhibitory effects on the pancreatic beta cells, leading to reduced insulin secretion, and the reduction in circulating growth hormone and insulin-like growth factor-1, resulting in reduced insulin requirements [ 38 ]. Rinzivillo et al [ 16 ] demonstrated HbA1C is associated with an increased risk of PEI development after commencing SSA therapy.…”
Section: Discussionmentioning
confidence: 99%